Molecular docking insights into Calophyllum-derived chromanones as potential EGFR and STAT3 inhibitors in cervical cancer: A review - Zaini, Nur Nabilah Mohd; Salleh, Wan Mohd Nuzul Hakimi Wan; Ghani, Nurunajah Ab; Salihu, Abubakar Siddiq; Nutho, Bodee; Eshboev, Farkhod; Tamfu, Alfred Ngenge (Edelweiss Applied Science and Technology, 2026)
Recently, chromanone compounds obtained from the Calophyllum species were found to exhibit anticancer properties in cervical cancer by inhibiting key cancerous proteins that are essential to cervical cancer progression and development. In this docking study, experiments were conducted against two key oncogenic targets in cervical cancer: the epidermal growth factor receptor (EGFR, PDB ID: 8A27) and STAT3 (PDB ID: 6NUQ). For EGFR, the mutant-selective allosteric inhibitor EAI045 was used as the positive control to match the allosteric conformation of the 8A27 structure. For STAT3, the SH2-domain suppressor STAT3 Inhibitor VII served as the control, consistent with the binding site captured in 6NUQ. Favorable interactions were observed with several compounds showing docking scores indicating strong binding affinity for EGFR kinase and STAT3 SH2 domain. Structural interaction analysis additionally exposed essential hydrogen bonding and hydrophobic contacts in the active sites. The results favor Calophyllum-derived chromanones as interesting lead compounds for dual targeting of EGFR and STAT3 pathways as an additional alternative for targeted therapies in cervical cancer. More importantly, it supports the ethnobotanical importance of Calophyllum species and illustrates the potential of computational techniques in converging traditional medicine for contemporary drug discovery.